New state, new citizens? Political change and civic continuities in the Low Countries, 1780-1830 - Pollmann, Judith; te Velde, Henk (BMGN - Low Countries Historical Review, 2018)
For half a century, historians of the Low Countries have studied the decades around 1800 as a period of radical transition. By way of historiographical introduction to this special issue, this article surveys both the national and international origins of this approach, assesses its consequences for our understanding of citizenship in the period, and argues for the need to add another perspective, that of continuity.This article is part of the special issue 'Political Change and Civic Continuities in the Age of Revolutions'. In de afgelopen vijftig jaar hebben historici van de Lage Landen de decennia rond 1800 vooral bestudeerd als een periode van radicale transitie. Bij wijze van historiografische inleiding op dit themanummer, geeft dit artikel een overzicht van de nationale en internationale ontwikkeling van deze benadering, en bekijkt welke consequenties die heeft gehad voor ons begrip van burgerschap in deze periode. Het betoogt dat er behoefte is een nieuw perspectief toe te voegen, dat van continuïteit. Dit artikel maakt deel uit van het themanummer 'Political Change and Civic Continuities in the Age of Revolutions'.